The Role of Tax Planning and Deferred Tax Expenses on Profit Management of Indonesian Food and Beverage Companies - Anggi Pratiwi Sitorus; Renika Hasibuan; Pasti Romauli Hutasoit (Cita konsultindo, 2024)
This research aims to analyze the role of tax planning and deferred tax burden on earnings management in food and beverage companies listed on the Indonesia Stock Exchange (BEI) with observations for the 2020-2022 period. The analytical method used in this research is the classical assumption test and multiple linear regression. The research results show that the tax planning variable has no effect on earnings management and the deferred tax expense variable has no effect on earnings management when tested partially. Simultaneously, tax planning and deferred tax expenses have a significant effect on earnings management in companies registered with BE.